SISTEM PENDUKUNG KEPUTUSAN PENENTUAN BONUS KARYAWAN MENGGUNAKAN METODE MULTI-ATTRIBUTIVE BORDER APPROXIMATION AREA COMPARISON (MABAC) - Ahmad; Mona Aprilia (CV. Multi Kreasi Media, 2024)
An employee is anyone who is able to do work to produce goods and services both to meet their own needs and those of the community, both inside and outside of work relations. In every company, agency, organization or business entity, they will provide a salary as compensation for an employee's work, in addition to providing a basic salary to their employees, each agency often provides a salary bonus. in determining bonuses for employees at PT Citra Prasasti Konsorindo, they still use Microsoft Excel assistance so that the process of determining bonuses that has occurred so far has not been accurate due to the large amount of data collected and the need for time to input data so that the company has difficulties in the process of determining employee bonuses. This causes delays for the company in providing an assessment. Given these problems, the researchers created a decision support system for determining employee bonuses at PT Citra Prasasti Konsorindo using the mabac method. The goal is to help the accuracy of the company in determining employee bonuses and make it easier for companies to input data and determine employee bonuses and provide time efficiency for companies in the process of determining employee bonuses. In this system there are employee data features, criteria, calculations and ranking as the final result which displays the ranking of employees who are entitled to receive bonuses. This research uses the method of observation, interviews and literature study. The design method used is waterfall and the testing technique used is blackbox. The final result of this system is the highest to lowest score and displays the recommendation ranking of employees who receive bonuses. Based on the test results, all existing pages and features are as expected and run according to their functions.